Novel Anti-Melanoma Immunotherapies: Disarming Tumor Escape Mechanisms - Sivan Sapoznik; Ohad Hammer; Rona Ortenberg; Michal J. Besser; Tehila Ben-Moshe; Jacob Schachter; Gal Markel (Clinical and Developmental Immunology)
The immune system fights cancer and sometimes temporarily eliminates it or reaches an equilibrium stage of tumor growth. However, continuous immunological pressure also selects poorly immunogenic tumor variants that eventually escape the immune control system. Here, we focus on metastatic melanoma, a highly immunogenic tumor, and on anti-melanoma immunotherapies, which recently, especially following the FDA approval of Ipilimumab, gained interest from drug development companies. We describe new immunomodulatory approaches currently in the development pipeline, focus on the novel CEACAM1 immune checkpoint, and compare its potential to the extensively described targets, CTLA4 and PD1. This paper combines multi-disciplinary approaches and describes anti-melanoma immunotherapies from molecular, medical, and business angles.